Adaptações e aspectos biomecânicos do complexo do ombro em jovens nadadores - Habechian, Fernanda Assis Paes (2017)
The swimming practice requires a great demand of the shoulder complex. The repetitive nature of this sport can lead to bone, muscular and kinematic adaptations. Studies analyzing these adaptations in young athletes are scarce in the literature. Researches in this area are important since it could provide knowledge about upper extremity functioning pattern and adaptations due to the swimming practice in this young population. Furthermore, it could help to develop prevention programs for shoulder injuries, focused in this population. In this way, the purposes of the thesis were: 1) to compare scapular kinematics, scapulothoracic muscle activation and shoulder muscles pressure pain threshold between children and adolescents non-athletes, amateur swimmers and competitive swimmers; and 2) to compare humeral retroversion in children and adolescents non-athletes, amateur swimmers and competitive swimmers and to analyze the relationship between swimming volume and the humeral retroversion in competitive swimmers. An electromagnetic tracking device, the Flock of Birds, was used to analyze the 3D scapular kinematics. To analyze the scapulothoracic muscle activation, an electromyography system Bagnoli-8 was used. To perform the pressure pain threshold a digital algometer was used. To quantify the humeral retroversion, a palpation method and measurement of the bicipital forearm angle were performed. In general, the results showed that competitive swimmers presented adaptations probably originated from the sport practice, such as increased scapular internal rotation and anterior tilt, higher muscle activation of the serratus anterior and increased humeral retroversion compared to non-athletes and amateurs. These results provide knowledge about musculoskeletal and biomechanics adaptations occurring in these young swimmers, allowing physical therapists and other professionals who are in contact with this population, to have a critical view regarding shoulder complex adaptations that may occur in young swimers.